Adaptation aux changements climatiques en milieu urbain et approche globale des trames vertes - Morgane Colombert; Philippe Boudes (VertigO)
Green infrastructure is used to promote a climate with a good quality, to improve the climate change adaptation or to increase biodiversity. Nowadays, climate, city and vegetation have to be mixed in a unique reflection. This combination is infrequent. So some experts on urban planning, atmospheric sciences, life sciences and sociology met to share and explain their point of view on the relation between climate, city and vegetation. These reflections are presented in this occasional publication.